Fenologi Pembungaan Dua Varietas Kelapa Sawit (Elaeis Guineensis Jacq.) di Kebun Pabatu PT. Perkebunan Nusantara IV - Izni Havira; Irfan Suliansyah; Wulan Kumala Sari (Program Studi Agroteknologi Fakultas Pertanian Universitas Andalas, 2022)
Oil palm has the prospect of rapid development in Indonesia, which causes an increase in plantation area to continue. However, the problem that is still encountered is the low productivity and quality of crop production. The solution that can be used is the use of planting material derived from superior varieties. High-yielding varieties are assembled through hybridization of two varieties that have the desired superior properties. Observation of the flower development cycle is needed as the basis for the hybridization process. Flower development is not only influenced by genetic factors, but also by environmental factors, especially climate. Observations on plant responses are part of a phenological study. This research was carried out in April-August 2021 at Pabatu Gardens, PTPN IV with the aim of observing the flowering phenology of the DxP 540 NG and DxP Socfindo MT Gano varieties. The climatic conditions of the research location during the observation were an average temperature of 29°C, 80% humidity, and an average rainfall of 145 mm/month. The average time required for the DxP 540 NG variety of male and female flowers, the growth phase of the sheath until the outer sheath broke, was 40 days and 38 days, the outer sheath broke until the inner sheath burst was 15 days and 18 days, the inner sheath broke to full bloom was 12 days. days and 16 days, and in full bloom until the flowers are completely pollinated, namely 4 days and 6 days. The average time required for the DxP 540 NG variety of male and female flowers in the growth phase of the sheath until the outer sheath breaks are 32 days and 30 days, the outer sheath breaks until the inner sheath bursts are 16 days and 15 days, the inner sheath bursts to full bloom, namely 11 days and 15 days, and in full bloom until the flowers are perfectly pollinated, namely 4 days and 6 days. The total time required for flowering for the male and female DxP 540 NG varieties was 71 days and 78 days, while for the DxP Socfindo MT Gano variety, male and female flowers were 63 days and 66 days, respectively.